2012
DOI: 10.1118/1.4749965
|View full text |Cite
|
Sign up to set email alerts
|

Is RapidArc more susceptible to delivery uncertainties than dynamic IMRT?

Abstract: Purpose: Rotational IMRT has been adopted by many clinics for its promise to deliver treatments in a shorter amount of time than other conventional IMRT techniques. In this paper, the authors investigate whether RapidArc is more susceptible to delivery uncertainties than dynamic IMRT using fixed fields. Methods: Dosimetric effects of delivery uncertainties in dose rate, gantry angle, and MLC leaf positions were evaluated by incorporating these uncertainties into RapidArc and sliding window IMRT (SW IMRT) treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 78 publications
(76 reference statements)
1
29
1
Order By: Relevance
“…The shift error has a negligible dosimetric impact, 0.1-0.2% deg À1 for OAR and 0-0.05% deg À1 for PTV, as shown by Betzel [31] for prostate and H&N RapidArc cases. Nevertheless, this systematic behavior was observed for other Varian machines [5,6].…”
Section: Discussionmentioning
confidence: 92%
“…The shift error has a negligible dosimetric impact, 0.1-0.2% deg À1 for OAR and 0-0.05% deg À1 for PTV, as shown by Betzel [31] for prostate and H&N RapidArc cases. Nevertheless, this systematic behavior was observed for other Varian machines [5,6].…”
Section: Discussionmentioning
confidence: 92%
“…Betzel et al [18] simulated the machine errors in both IMRT and VMAT plans and compared the 3D patient dose distributions after feeding back the modified plans to the treatment planning system. They found that the VMAT plans is less susceptible than IMRT plans on the gantry angle error than the MLC error, which was supported by their Delta 4 analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The mean leaf gap in VMAT is often larger than that in IMRT, (26) so that the dose agreement for VMAT will likely be higher. However, it was also observed that the leaf gaps in VMAT plans could be widely distributed from small to large; another fact is that the aperture size in the longitudinal direction may not be consistently larger in VMAT plans than in IMRT plans.…”
Section: Discussionmentioning
confidence: 99%